Schoolchildren survey and community survey for the determination of seroprevalence against IgM anti phenolic glycolipid-I antibody in leprosy endemic areas, South Sulawesi, Indonesia (Faculty of Medicine Universitas Indonesia, 1996)
[no abstract available]